Emotions in Charter School Teaching: Three Stories From Year One (LEARNing Landscapes, 2018)
The purpose of this paper is to illuminate the experiences of two recent graduates from an undergraduate initial certification educator preparation program (EPP) who began their first year working for a charter school in a large urban city. Their background in the constructivist-oriented EPP contrasts sharply with the philosophy and instructional practices of the charter school. The extreme nature of this particular context sheds light on the teacher induction process and raises questions about enhancing new teachers’ adaptive capacities and emotional resilience to work through professional dissonance in the first years. These stories suggest that new teachers may benefit from additional training in communication skills and emotion management in the navigation of school workplace dilemmas.
Keywords: Teach for America; teacher induction; principled resistance; emotions in teaching